Evaluating the Effectiveness of Contextual and Problem-Based Learning Approaches in the Pedagogical Practice of Christian Religious Education - Roy Kolibu, Dirk; Stepanus, Stepanus (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to evaluate the implementation of Contextual Teaching and Learning (CTL) and Problem-Based Learning (PBL) models within the Community Service Program (PPkM) in the Christian Religious Education (CRE) course at the Universitas Kristen Indonesia. Using a descriptive quantitative approach, the research involved 393 students across eight faculties who had participated in the PPkM initiative. The findings reveal that applying CTL and PBL significantly supports achieving CRE learning objectives by enhancing students’ cognitive, affective, and psychomotor domains. Moreover, these pedagogical models foster students' ability to reflect their faith through tangible actions, positioning the learning environment as a contextual and transformative ministry space. Evaluation scores averaged from “good” to “very good,” indicating that service-based learning effectively bridges the gap between theory and practice. This research offers a vital contribution to the development of a Christian Religious Education curriculum that is contextually relevant and responsive to the dynamics of Indonesia’s multicultural society